2004
DOI: 10.1016/j.jcat.2004.08.019
|View full text |Cite
|
Sign up to set email alerts
|

The selectivity of -hexane hydroconversion on MOR-, MAZ-, and FAU-type zeolites

Abstract: Analyses of a series of published n-hexane hydroisomerization product slates suggest that MAZ-type zeolites yield more dimethylbutane and less methylpentane than either FAU-or MOR-type zeolites. Molecular simulations do not corroborate the traditional view that these selectivity differences are specifically related to the MAZ-, FAU-, or MOR-type zeolite topology. A scrutiny of the literature indicates that reported variation in selectivity relates to a variation in the efficiency of the (de)hydrogenation funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 65 publications
0
22
0
Order By: Relevance
“…32 When a zeolite facilitates formation of a reaction intermediate, the Brønsted-Evans-Polanyi principle does not necessarily apply, 32 so that formation of a reaction intermediate can be facilitated without affecting the ease of formation of the transition state. 489 channels irrespective of the absence or presence of mass transfer limitations. 381 …”
Section: Transition State Shape Selectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…32 When a zeolite facilitates formation of a reaction intermediate, the Brønsted-Evans-Polanyi principle does not necessarily apply, 32 so that formation of a reaction intermediate can be facilitated without affecting the ease of formation of the transition state. 489 channels irrespective of the absence or presence of mass transfer limitations. 381 …”
Section: Transition State Shape Selectivitymentioning
confidence: 99%
“…Interestingly, without C 16 one does not observe an optimal selectivity toward dimethylbutane. 489 In contrast to transition-state selectivity, reaction intermediate shape selectivity requires severe mass transfer limitations between gas and adsorbed phases.…”
Section: Transition State Selectivitymentioning
confidence: 99%
“…In fact, several shape-selective transformations catalysed by zeolites have been re-analysed using the principles we have outlined above, resulting in the identification of selectivity mechanisms different from those proposed originally [19][20][21][22][23] .…”
mentioning
confidence: 99%
“…Thus, severe mass transfer limitations between the gas and adsorbed phases are a prerequisite for this type of reaction-intermediate shape selectivity to occur. In the absence of mass transfer limitations, FAU-, MAZ-, and MOR-type zeolites yield a virtually identical C 6 isomer product slate [120]. Whether the optimum branched isomer yield reported for MAZ-and AFI-type zeolites is indeed only a result of reaction-intermediate shape selectivity remains the subject of debate.…”
Section: Gas-phasementioning
confidence: 99%
“…Recently, it was suggested that transitionstate shape selectivity might also contribute [118]. If there is indeed a contribution, it must be small as an optimized MAZ-type zeolite yields the same yield ratio of 2,3-dimethylbutane and n-hexane in the hydrocracking of n-hexadecane as do FAU-or MOR-type zeolites [120]. In addition, it was found that 2,3-dimethylbutane diffuses faster than other hexane isomers in MOR-as compared to FAU-type zeolites [121].…”
Section: Gas-phasementioning
confidence: 99%